Developing a low-cost dermatoscope - Ng, Julia Poh Hwee (2017)
Dermatoscopes play a burgeoning role in dermatology, but are prohibitively expensive for non-dermatologists, especially medical undergraduates and generalists in resource-poor settings. A low-cost solution lies in developing a smartphone-adapted dermatoscope via three-dimensional printing, which further reduces cost with its affordable raw materials and self-assembly requirements. The prototype dermatoscope has fulfilled its low-cost appeal and trumps existing dermatoscopes in attaining instant and consistent image focus; the percentage of medical students keen on prototype ownership was manifold above commercial dermatoscope ownership rates. Future revisions of the prototype need to improve image resolution, enable smartphone model adaptability and simplify self-assembly to enhance actual ownership. It is a promising device in enhancing dermatological care spanning geographical boundaries and skill level.